CD8+ T-Cell Repertoire in Human Leukocyte Antigen Class I-Mismatched Alloreactive Immune Response - Bettens, Florence; Calderin Sollet, Zuleika; Buhler, Stéphane; Villard, Jean (Frontiers in Immunology, 2021)
In transplantation, direct allorecognition is a complex interplay between T-cell receptors (TCR) and HLA molecules and their bound peptides expressed on antigen-presenting cells. In analogy to HLA mismatched hematopoietic stem cell transplantation (HSCT), the TCR CDR3β repertoires of alloreactive cytotoxic CD8+ responder T cells, defined by the cell surface expression of CD137 and triggered in vitro by HLA mismatched stimulating cells, were analyzed in different HLA class I mismatched combinations. The same HLA mismatched stimulatory cells induced very different repertoires in distinct but HLA identical responders. Likewise, stimulator cells derived from HLA identical donors activated CD8+ cells expressing very different repertoires in the same mismatched responder. To mimic in vivo inflammation, expression of HLA class l antigens was upregulated in vitro on stimulating cells by the inflammatory cytokines TNFα and IFNβ. The repertoires differed whether the same responder cells were stimulated with cells treated or not with both cytokines. In conclusion, the selection and expansion of alloreactive cytotoxic T-cell clonotypes expressing a very diverse repertoire is observed repeatedly despite controlling for HLA disparities and is significantly influenced by the inflammatory status. This makes prediction of alloreactive T-cell repertoires a major challenge in HLA mismatched HSCT.